A values-driven academic affiliation between a public medical school and a private healthcare provider: exploring the perceptions of key opinion leaders - Du Preez, Leon; Otaki, Farah; Clemens, Timo; Al-Hammadi, Suleiman; Stanley, Adrian; Ho, Samuel B.; Kilian, Paddy; Loubser, Pietie; Bayoumi, Riad; Ezimokhai, Mutairu; Bedford, Barry; Fathey, Tarek; et al. (Frontiers in Health Services, 2025)
IntroductionIn an Academic Health System model where university and clinical care institutions are separate entities, robust agreements are needed for effective working relationships among the involved institutions. There is paucity in the literature around reports of such affiliations, especially those relating to public private partnerships. Accordingly, the overall purpose of this study is to explore the perception of key opinion leaders about the development of a values-driven affiliation between a public medical school and a private healthcare provider in the first integrated Academic Health System in Dubai, United Arab Emirates, namely: Dubai Health. The process of developing the respective affiliation is based on the principles of action research. It involved ongoing cycles of planning, acting, observing, and reflecting.MethodsThis study relied on a qualitative phenomenological research design, where 18 primary stakeholders, who played an active role in making the affiliation, were given the option of providing their feedback either in writing, using a tailor-made questionnaire, or in the form of a semi-structured interview. Constructivist epistemology constituted the basis of the entailed interpretive qualitative analysis, which followed the six-step analysis approach initially introduced by Braun and Clarke (2006).ResultsThe qualitative analysis led, as per this study's conceptual framework: “Public Private Affiliation Journey”, to two interconnected themes, namely: Key Milestones and Driving Forces. Within Key Milestones, seven sequential categories were identified: Observing a triggering need, Finding a good match, Seizing the opportunity, Arriving at a common ground, Looking ahead, Venturing for the right reasons, and Reaping the benefits. Within the second theme: Driving Forces, the following three categories were identified: Aspiring for success, Leveraging human qualities, and Doing things the right way.DiscussionThis study showed that there is a latent potential in forming public private partnerships that can enable the formation and development of Academic Health Systems. It also showed how the guidelines of action research can be set as the basis of the process of partnership formation, and how following those guidelines in such an endeavor maximizes value for all. In addition, it clearly brought forth the importance of having a robust governance structure with committed and engaged leadership, and clear communication channels, and of equipping the physicians with the skills needed to be effective educators. Lastly, this study introduced the “Public Private Affiliation Journey” conceptual framework, which can be deployed in “federated” Academic Health Systems worldwide to increase the chances of success of public private partnerships and to maximize the value attained through them.